1966
DOI: 10.1021/bi00867a028
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrofolate Reductase from the L1210R Murine Lymphoma. Fluorometric Measurements of the Interaction of the Enzyme with Coenzymes, Substrates, and Inhibitors*

Abstract: The quenching of protein fluorescence that occurs when dihydrofolate reductase is titrated with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
38
1

Year Published

1967
1967
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 22 publications
(14 reference statements)
8
38
1
Order By: Relevance
“…The formation of binary complexes between the enzyme and a variety of substrates and inhibitors can Table 5 is comparable with the values found for the enzyme from E. coli (2.4 x 106M-1, Erickson & Mathews, 1973; 9 x 105 M-1, Greenfield et al, 1972), T4 phage (2.0x 106M-1; Erickson & Mathews, 1973) and L1210 lymphoma (5.Ox 106M-1; Perkins & Bertino, 1966). NADPH 1976 appears to bind appreciably more tightly to the L. casei enzyme than to these other enzymes, for which binding constants in the range 1.3 x 106-2 x 107 M-1 were reported.…”
Section: Binding Ofsubstrates and Inhibitorssupporting
confidence: 83%
“…The formation of binary complexes between the enzyme and a variety of substrates and inhibitors can Table 5 is comparable with the values found for the enzyme from E. coli (2.4 x 106M-1, Erickson & Mathews, 1973; 9 x 105 M-1, Greenfield et al, 1972), T4 phage (2.0x 106M-1; Erickson & Mathews, 1973) and L1210 lymphoma (5.Ox 106M-1; Perkins & Bertino, 1966). NADPH 1976 appears to bind appreciably more tightly to the L. casei enzyme than to these other enzymes, for which binding constants in the range 1.3 x 106-2 x 107 M-1 were reported.…”
Section: Binding Ofsubstrates and Inhibitorssupporting
confidence: 83%
“…A decrease in NADPH levels is significant for the function of DHFR as this coenzyme protects DHFR from proteolysis. 18,19 Inhibition of NADK contributes to decreased levels of NADPH and NADP, however whether or not BR inhibits other pathways involving NADPH/NAD + should be considered. The cytotoxicity of BR on CEM/S cells and its effect on cell cycle distribution as a function of BR concentration at 24 and 48 h showed that at higher concentrations an increase in the percent of cells in the S-Phase occurred with increasing numbers of subG-1 cells (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…17 Earlier studies from this and other laboratories had shown a critical role for NADPH in protecting DHFR from proteolysis. 18,19 Further, lowered levels of intracellular levels of DHFR increase the susceptibility of cells to methotrexate, a powerful stoichiometric inhibitor of this enzyme. BR is converted to benzamide adenine dinucleotide (BAD) in cells and has been shown to be a potent inhibitor of NAD Kinase.…”
mentioning
confidence: 99%
“…The formation of binary and ternary complexes of dihydrofolate reductase with cofactors, substrates, and drugs has been examined by a wide variety of techniques including UV absorption (11)(12)(13), fluorescence (14,15), circular dichroism (16), and NMR spectroscopy (17,18). In general, these studies confirmed the tightness of binding and, in addition, suggested the possibility of conformational changes in the enzyme associated with the binding process.…”
mentioning
confidence: 93%